The Reflection of Ethics Education on Clinical Practices in Undergraduate Nursing Education: A Qualitative Study (Bangladesh Journal of Medical Science, 2022)
Aim:This research aims to reveal the reflections of ethics education given to nursing students in undergraduate education on clinical practices.Method: A focus group interview from qualitative methods was held to obtain and interpret information regarding the reflections of ethics courses. Fifteenvolunteernursing students studyingatthe faculty of health sciences ofa public university in Turkey were included in the research. For the data analysis, the method used to code and categorizefocus group data were adapted from approaches to qualitative data analysis.Results: Six main themes emerged from the data: (1) opinions about ethics courses; (2) ethical issues; (3) the factors that cause ethical issues; (4) the effects of ethics courses on the approach towards ethical problems; (5)contradictory situations between the ethics course and clinical practices; (6) recommendationsabout the ethics course and educators.Conclusion:According to the data obtained in this study, the researcher concluded that the lecturers and teaching methods used are important in ethics education in nursing.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 711-718